ANALYSIS OF FAKTORS OF MATERNAL MORTALITY RATE IN MEDAN CITY USING BIVARIAT POISSON REGRESSION - Anita Ningsih Sirait; Ersya Nurul Fairuz; Khairun Nikmah; Tesya Yunita Sembiring (Pena Cendekia Insani, 2021)
There are several factors that cause maternal death, such as bleeding,hypertension, infection, prolonged labor, abortion and others. Maternal deathsrelated to pregnancy, childbirth and the puerperium (42 days after delivery),and the number of deaths per 100,000 live births related to pregnancy ormedical problems (except accidents or incidents). In this study the case ofmaternal mortality using the Bivariate Poisson Regression model which aims todetermine what factors are the main factors in maternal mortality using theBivariate Poisson regression method.